CONDITIONS FOR THE DEVELOPMENT OF LEADERSHIP QUALITIES OF FUTURE PSYCHOLOGISTS IN THE PERIOD OF MARTIAL LAW WITH THE APPLICATION OF VALEOLOGICAL PRINCIPLES - Pavliuk, Oksana (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2023)
The purpose of the article is to study the set of conditions and peculiarities of the development of leadership qualities of future psychologists in the post-quarantine stage during martial law with the application of valeological principles. The relevance of the research is determined by the realities of toda’s events, the socio-economic, political, socio-psychological situation in Ukraine and beyond. In the presented article, we implemented the relevant tasks: based on the analysis of domestic and foreign literature, we singled out a set of conditions that contribute to the development of leadership qualities of future psychologists; described the features of the development of these qualities; outlined the importance of developing a valeological worldview in the process of formation and development of leadership qualities; characterized the functions and principles of valeological science, which is a determinant for the conditions in our study. The research procedure is presented on a complex of scientific methods of analysis, structuring and synthesis, direct observation and systematization. The method of logical generalization was used for theoretical substantiation of the tasks. The result of the study was confirmation of the possibility of developing the leadership qualities of future psychologists in institutions of higher education during the period of martial law The complex of conditions that ensure the development of relevant qualities was singled out and described, the importance of the development of a valeological worldview in the process of development of leadership qualities in psychology students was emphasized and outlined. The conclusions of our research are presented in the conclusions, showing the necessity and importance of developing the leadership qualities of future psychologists in higher education institutions with the improvement and expansion of the valeological worldview. It is noted that in order to implement our task, it is necessary to create and ensure a set of conditions, namely: psychological- pedagogical, psychological-supervisory, social-psychological and individual- oriented conditions that will ensure the development of relevant qualities, the importance of developing a valeological worldview in students is emphasized andoutlined. The importance of valeological science in the context of our research is emphasized, its functions, application and implementation of the principles of this science are described